1998
DOI: 10.1097/00006534-199809030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Correction of Orbital Neurofibromatosis

Abstract: Neurofibromatosis is a systemic disease that often produces striking disfigurement. Orbital manifestations are common and include sphenoid dysplasia with or without infiltration of the periorbital soft tissues. The resultant deficiency of the posterolateral orbital wall may lead to protrusion of the temporal lobe into the orbit, displacement of the globe, and pulsatile exophthalmos. Treatment at our unit has consisted of transcranial orbital reconstruction with bone grafts and periorbital soft-tissue correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…This should be considered on a case by case basis and is a more critical issue when associated with a seeing eye. 63 …”
Section: Introductionmentioning
confidence: 99%
“…This should be considered on a case by case basis and is a more critical issue when associated with a seeing eye. 63 …”
Section: Introductionmentioning
confidence: 99%
“…Autogenous bone graft was originally used for the repair of the skull base defect, but the problem of bone resorption following surgery has been mentioned by many authors in the literature [7, 8]. Snyder et al[ 7] reviewed their results in 14 patients who had undergone transcranial repair with autogenous bone graft in a period of follow-up ranging from 6 to 17 months and found that recurrent globe pulsation following initial resolution was observed in 4 patients. They also observed that partial or complete loss of bone could be found even after rigid fixation of grafts in a well-vascularized recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of bone graft resorption remains unclear. Snyder et al[ 7] suggested that the problem might be related to pulsation of the temporal lobe, tumor erosion and the nature of the local environment (soft tissue dysplasia). However, the osseous quality of the graft may also play an important role [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations